Prototipe Sistem Informasi Haji Untuk Menangani Jemaah Tersesat Menggunakan SMS Gateway - Sugiyanto (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
The establishment of a special sector of security around the Masjidil Haram Grand Mosque and the addition of security personnel in every sector of the lodging of pilgrims is clear evidence that the Indonesian government undertake serious efforts to improve the organization of the Hajj, however, the officers still overwhelmed in dealing with pilgrims lost / missing which can reach hundreds of people every next. This study aim to solve the problem of handling the assembly lost / missing by eveloping an information system that involves sms gateway application as an inexpensive technology procurement, distribution process information fast, and easy to use. Two kinds of tests performed on the system, ie functional test and broadcast test. Functional test is useful to determine the suitability of the design process with the results of the implementation. While the broadcast test was conducted to determine weaknesses sms gateway server system.